Submarine Lateglacial lake deposits from the Kattegat, southern Scandinavia. (17th February 2019) - Wiberg‐Larsen, Peter; Bennike, Ole; Jensen, Jørn Bo
ABSTRACT: Lateglacial submarine lake sediments are reported for the first time from the Kattegat Sea in southern Scandinavia. The Lateglacial sediments were collected from a vibrocore that contained, from top to bottom, Holocene marine muddy sand, Holocene brackish‐water mud, Early Holocene peat with remains of Betula pubescens and telmatic plants, Lateglacial lake deposits that are the focus of this paper, and homogenous sand. Radiocarbon dating of terrestrial plant remains from the Lateglacial sediments gave ages between 12 400 and 12 800 cal a bp, corresponding to the Younger Dryas. The Lateglacial sediments contain remains of Betula nana and other plants indicating a tundra‐like open landscape with dwarf shrub heaths, which is typical for the region. Remains of macrolimnophytes indicate shallow carbonate‐rich, cool lake waters. Remains of larvae of Trichoptera and Chironomidae dominate the invertebrate fauna and indicate a fairly species‐rich fauna. Half of the trichopteran taxa today have their distribution north of Denmark or show a generally northern distribution in Europe. The lake sediments are found at ∼ 24 m below sea level, and the presence of lake sediments shows that this part of Kattegat had not been transgressed by the sea during the Younger Dryas.